Hard magnet topological semimetals in XPt3 compounds with the harmony of Berry curvature - Anastasios Markou; Jacob Gayles; Elena Derunova; Peter Swekis; Jonathan Noky; Liguo Zhang; Mazhar N. Ali; Yan Sun; Claudia Felser (Communications Physics, 2021)
Topological magnetic semimetals can realise large intrinsic anomalous Hall effects using the characteristics of their electronic band structure and Berry curvature. Here, the authors predict an anomalous Hall effect for cubic CrPt3 using first principle calculations and confirm the results experimentally.